Pengaruh Merger dan Akuisisi Terhadap Financial Performance pada Sektor Transportasi di ASEAN - Gracia Stefani; Juniarti Juniarti (Business Accounting Review, 2021)
This research aims to study the influence of cost-leadership strategy on sustainable financialperformance in South East Asia. The control variables used in this research were Market Share(MS), Competition Intensity (CI), and Firm Size (SIZE). The sample in this research consisted of 656companies on all sectors listed on the South East Asian Stock Exchange in the 2015 – 2019 period.All variables were measured with ratio scale. Cost-leadership strategy was measured by the ratio ofemployee to assets. The data analysis technique used was panel data regression which processedwith GRETL software and the Random Effect Model (REM) was obtained as the selected estimationmodel. The result of this research showed that cost-leadership strategy positively influencedsustainable financial performance if measured with employee to assets. Market share and firm sizehad a positive and insignificant influence on sustainable financial performance. Meanwhile,competition intensity had a negative and insignificant influence on sustainable financialperformance.